LANGUAGE CHOICE AMONG FEMALES IN EQWIP HUBS COMMUNITY - TRINANDA NUR, BELA (LANGUAGE HORIZON, 2019)
Keywords: Language choice, women language features Language choice is a phenomenon that is common in multilingual societies. Language encounters that happen over and over can create a bilingual or multilingual group. This research is motivated by the use of the diversity of language codes used by members of the EQWIP HUBs community. EQWIP HUBs is a community in surabaya build by volunteers from Canada. The purposes of this study are 1) to describe the form of language choice and explain the factors that determine the language choice in this community, 2) to know what personal reason that makes them use different languages and 3) to describe what women language feature use in this community and how they enhance English language by using women linguistic features. This study examines the sociolinguistic perspective on language choice in the EQWIP HUBs community based on Hymes? theory known as the SPEAKING acronym, such as (1) setting and scene (2) participants, (3) ends, (4) act sequence, (5) keys, (6) instrumentalities, (7) norms, and (8) genre. The last problem use Lakoff theory about women language features. The method used in this research is qualitative method. Some steps has been done such as, observation, interview and transcribe. The result of this study state that English is the main language used in this community because of the rules set by the community and presence of the native speaker. Language choice from three languages, English, Indonesian and Javanese is only done by the members. This research acknowledges that language choice can only be made by a multilingual or bilingual group. All members in this community are multilingual people who speak three languages and they use the three languages with different interlocutors.